2023
DOI: 10.3390/app13169343
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Metal–Organic Frameworks and Their Derivative Electrocatalysts for Water Splitting

Lin Shen,
Yongteng Qian,
Zhiyi Lyu
et al.

Abstract: The escalating urgency to mitigate climate change and enhance energy security has prompted heightened exploration of hydrogen production via electrocatalysis as a viable alternative to conventional fossil fuels. Among the myriad of electrocatalysts under investigation, two-dimensional (2D) metal–organic frameworks (MOFs) stand out as a particularly appealing option. Their unique properties, including a large active specific surface area, distinctive pore structure, ample metal active sites, ultra-thin thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 192 publications
0
5
0
Order By: Relevance
“…Regarding the characterization of 2D MOFs, XAS and XPS are widely employed techniques, as they can offer comprehensive insights into their valence state, chemical environment, surface composition, and electronic structure of elements. [ 57,153 ] The unique configuration of MOFs, which involves the coordination of metal ions or clusters with organic ligands or linkers, enables the utilization of other spectroscopic techniques, such as UV–vis, [ 154 ] ATR‐FTIR, SEIRAS, and FTIR, [ 155–157 ] and Raman spectroscopy, [ 109 ] to investigate information on target products, intermediates, electrode‐surface bonding, the crystal phase structure or phase change, the oxidation state, and the coordination and polymerization state of metal catalytic units. To make the experimental data more reliable, other techniques, such as contrast experiments, DFT calculations, and HRTEM, are often supplemented for the identification of active sites for 2D MOFs.…”
Section: Identification Of Active Sites In 2d Mof Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the characterization of 2D MOFs, XAS and XPS are widely employed techniques, as they can offer comprehensive insights into their valence state, chemical environment, surface composition, and electronic structure of elements. [ 57,153 ] The unique configuration of MOFs, which involves the coordination of metal ions or clusters with organic ligands or linkers, enables the utilization of other spectroscopic techniques, such as UV–vis, [ 154 ] ATR‐FTIR, SEIRAS, and FTIR, [ 155–157 ] and Raman spectroscopy, [ 109 ] to investigate information on target products, intermediates, electrode‐surface bonding, the crystal phase structure or phase change, the oxidation state, and the coordination and polymerization state of metal catalytic units. To make the experimental data more reliable, other techniques, such as contrast experiments, DFT calculations, and HRTEM, are often supplemented for the identification of active sites for 2D MOFs.…”
Section: Identification Of Active Sites In 2d Mof Catalystsmentioning
confidence: 99%
“…In recent years, some reviews have been reported on the research progress of 2D MOFs, 2D MOF‐based materials, or their derivatives, mainly focusing on the synthesis strategies and applications. [ 54–60 ] To the best of our knowledge, there is currently a lack of comprehensive reviews dedicated to the identification of active sites and modulation of electronic structure for 2D MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding, the stability of such organodisulfides remains a significant concern as evidenced from the CV processes (Figure S2), and there might be some unfavorable parasitic reactions for them. 38,39 A three-electrode setup was used, where working, counter and reference electrodes were glass https://doi.org/10.26434/chemrxiv-2024-2pjxx ORCID: https://orcid.org/0000-0002-4710-8815 Content not peer-reviewed by ChemRxiv. License: CC BY-NC-ND 4.0 carbon (3 mm), platinum (Pt) foil and Pt wire, respectively.…”
Section: Functional Group Tuningmentioning
confidence: 99%
“…The synergistic impact of the MOF and conductive substrates is recognized as a key factor contributing to the success of MOF-based composite electrocatalysts. 8 In fact, these cooperative interactions can be explored in more depth to boost the catalytic performance of the MOFs toward OER and HER reactions. Apart from the synergistic interaction of MOF and substrate, this phenomenon may also operate in the intermolecular synergistic effect between the two different MOFs mixed together, and intramolecular synergies may arise when two different metallic clusters within a multimetallic MOF interact.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, MOF-based electrocatalysts have the potential to generate synergistic effects to increase the catalytic performance. The synergistic impact of the MOF and conductive substrates is recognized as a key factor contributing to the success of MOF-based composite electrocatalysts . In fact, these cooperative interactions can be explored in more depth to boost the catalytic performance of the MOFs toward OER and HER reactions.…”
Section: Introductionmentioning
confidence: 99%